Doubling farmers' income: A promising target fraught with challenges - Bathla, Seema; Kumar, Anjani; Kumar, Navneet; Hussain, Siraj (India International Centre, 2025)
The agricultural sector in India continues to be the major source of livelihood and employment. It contributes 19 per cent to the gross domestic product (GDP) but has a much higher share in total employment at 46.1 per cent. During the sudden lockdown imposed on 20 March 2020 during the COVID-19 pandemic, it was the agriculture and rural sectors that ensured food security to the nation and sustained millions of migrants from cities and towns. While other sectors of the economy were highly stressed, agriculture provided succour to the families affected by the loss of job, income and livelihood.